WMS implementation phases: case study in furniture retail - Antonio da Silva Costa, Walter; Alcides Gobbo Júnior, José (Revista Gestão da Produção Operações e Sistemas, 2008)
One of the critical phases in physical distribution is the management and administration of products that are stored in warehouses. The Warehouse Management System (WMS) is a specialized system that manages warehous operations, attempting to meet the inherent needs of these operations. This way, many companies adopt these systems in order to improve logistics operations and the management of warehouses. The main objective of this study is to present an implementation planning methodology of WMS in warehouses. A study was conducted on a large-scale retail company in the Brazilian furniture sector. The company adopted a WMS to work together with the organizations ERP in their warehouse. Considering the potential for operational improvement, this study aims at providing the practitioners with a study which shows that, with good implementation and correct use of the WMS, significant profits can be obtained. The result of this study is the definition of implementation phases for a WMS in warehouses. Keywords: WMS, ERP, warehouse, logistic, storage.